2006
DOI: 10.1097/01.nrl.0000195831.46000.2d
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia

Abstract: Recent advances in molecular biology have led to the discovery of novel dystonia genes and loci, updating classification schemes, and better understanding of underlying pathophysiology. Treatment strategies for dystonia have significantly been updated with the introduction of different forms of botulinum toxin therapy, new pharmacologic agents, and most recently pallidal deep brain stimulation. A systematic approach to the diagnosis and treatment evaluation of dystonic patients provides optimal care for long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Maraganore's research found that ubiquitin carboxy-terminal hydrolase L1 (UCHL1) was a susceptibility gene for PD and a potential target for disease-modifying therapies [ 12 ]. However, these genes expression profiles could not be analyzed in brain during life and were mainly obtained in PD subjects accompanied with classic motor symptoms [ 13 ]. Similarly, clinic diagnosis is hard to made before these signs and symptoms appear.…”
Section: Introductionmentioning
confidence: 99%
“…Maraganore's research found that ubiquitin carboxy-terminal hydrolase L1 (UCHL1) was a susceptibility gene for PD and a potential target for disease-modifying therapies [ 12 ]. However, these genes expression profiles could not be analyzed in brain during life and were mainly obtained in PD subjects accompanied with classic motor symptoms [ 13 ]. Similarly, clinic diagnosis is hard to made before these signs and symptoms appear.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained muscle contractions trigger repetitive abnormal movements or abnormal postures [1,2]. Dystonia may occur idiopathically or as a secondary symptom due to a certain type of disease or condition [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia may occur idiopathically or as a secondary symptom due to a certain type of disease or condition [3]. It can be treated with dopaminergic drugs, anti-cholinergic drugs, or botulinum toxin muscle relaxants [1,4]. Neuroablative surgery, such as thalamotomy or pallidotomy and deep brain stimulation (DBS), can be performed if generalized dystonia does not respond to conservative treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that dystonia is an inherited disorder and is age-onset dependent, considered as primary dystonia, since no neurological lesions have been found in association with the disorder (Bhidayasiri, 2006[ 5 ]). Some cases of dystonia may accompany other neurological disorders such as brain injury or Parkinson's disease; they are categorized as secondary dystonia (Breakefield et al, 2008[ 6 ]).…”
Section: Introductionmentioning
confidence: 99%